Geochemistry of Amphibolites in Akom II, Nyong Series, North Western Border of the Congo Craton, South Cameroon - Anehumbu Aye, Beyanu; Azinwi Tamfuh, Primus; Tata, Enerst (International Journal of Advanced Geosciences, 2021)
The garnet amphibolites, from the Akom II area in the Archaean Congo Craton, were examined to determine the geochemical affinity and tectonic environment. The study uses mineral assemblages and whole-rock geochemistry to identify the geochemical affinity and tectonic setting of the amphibolites associated with monzogabbro and pyroxenites. The studied rocks of Akom II are garnet amphibolites. Mineralogically, the rocks contain hornblende + plagioclase + garnet ± quartz ± epidote ± apatite ± opaque, indicating that they could have been formed from a basic igneous protolith. The geochemical signature indicates that the rocks are tholeiitic in nature. They are similar to the metamorphosed equivalents of ocean island basalts (OIB), with characteristics typical of Volcanic Arc-Basalt (VAB). The geotectonic diagrams confirm the tholeiitic nature of these amphibolites. High field strength elements ratios (Nb/Ta) range from 14-16, which corresponds to Volcanic Arc Basalt (VAB). The primitive mantle normalized patterns of these rocks show negative anomalies in Ta and Ti suggesting a geotectonic signature characteristic of a subduction zone, consequently suggesting the existence of a suture zone in the study area.